Estrogen receptor 1 gene variants and estradiol activities in alcohol dependence - Mühle, Christiane; Barry, Brianna; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2019)
Objective: Alcohol use disorders inflict a great individual and societal burden. Although sex hormone effects have been implicated in alcohol dependence, research has mostly neglected estrogen activities and female alcohol- dependent patients. Here, we investigated associations of estrogen receptor 1 (ESR1) genetics and serum estradiol activities with aspects of alcohol dependence.
CRIS-Team WoS Importer:2019-05-24